"THE PLIGHT OF WOMEN FISH VENDORS IN TAMIL NADU: CHALLENGES AND SOLUTIONS" - Dr. M. Rajeswari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract Women fish vendors in Tamil Nadu play a significant role in the fishing industry's supply chain, from catching to selling fish. However, they face various challenges that impact their livelihood and well-being. This paper aims to explore the challenges faced by women fish vendors in Tamil Nadu and identify potential solutions to address their plight. The paper highlights the lack of access to resources, health hazards, social stigma, and lack of legal protection as major challenges faced by women fish vendors. The paper suggests solutions such as providing access to capital, improving infrastructure and technology, ensuring health and safety, and providing legal protection to empower women fish vendors.